Kinerja Kepala Sekolah dalam Membina Profesionalisme Guru di UPT SD Negeri 141 Gresik - Kudariyanto Kudariyanto; Ashari Ashari (Universitas Maritim AMNI Semarang, 2023)
The findings and analysis of the research are, 1) The Principal's Performance in Fostering Teacher Professionalism at UPT SD Negeri 141 Gresik includes: peer tutor assistance, training and workshops, mentoring and collaboration, observation and feedback, curriculum development, research and innovation, use of technology, discussion and reflection, qualification improvement, and career plan development; 2) Forms of teacher professionalism include: continuous development, commitment to students, reflection and renewal, professional ethics, collaboration, involvement in decision-making, use of technology, effective classroom management, monitoring and evaluation of students, communication with parents, development of learning materials, career development, and involvement in school activities; 3) Supporting factors include: school management support, resources, school culture, effective communication, professional development programs, constructive performance appraisal, rewards and recognition, understanding of teachers' needs; and inhibiting factors include: limited resources, resistance to change, unclear vision and goals, internal conflicts, time pressure, curriculum incompatibility, high administrative demands, uncertainty of the school environment. In general, school principals must provide professional services in the field of education in order to organize the educational process effectively and efficiently.